Effect of Telephone Counseling on Continuity and Duration of Exclusive Breastfeeding after Cesarean Delivery: A Clinical Trial - Khadijeh Sarayloo; Zahra Vafaeenezhad (مجله دانشگاه علوم پزشکی گرگان, 2023)
Background and Objective: Breast milk has significant benefits for both mothers and babies. Counseling is a beneficial method for the continuity of exclusive breastfeeding. Remote counseling methods are currently being developed. This study was conducted to determine the effects of telephone counseling on the continuity and duration of exclusive breastfeeding among mothers who have had a cesarean section. Methods: In this clinical trial, 154 mothers who have had cesarean section delivery were randomly divided into an experimental and a control group. The intervention group received seven sessions of telephone counseling for 1-3 months postpartum in addition to the routine breastfeeding training program. The control group only received the routine breastfeeding training program. Results: After 4 months postpartum, the average duration of exclusive breastfeeding in the intervention group (15.51±0.88 weeks) was longer than that in the control group (10.74±5.33 weeks) (P<0.05). At 3 months postpartum, exclusive breastfeeding in the intervention group was 10.45 times longer than in the control group (OR=10.455, CI=2.547-42.912, P<0.001). Conclusion: Telephone counseling is effective in increasing the continuity and duration of exclusive breastfeeding in mothers who undergo a cesarean section.